If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.5(8x + -6) = 6x + -7 Reorder the terms: -0.5(-6 + 8x) = 6x + -7 (-6 * -0.5 + 8x * -0.5) = 6x + -7 (3 + -4x) = 6x + -7 Reorder the terms: 3 + -4x = -7 + 6x Solving 3 + -4x = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -4x + -6x = -7 + 6x + -6x Combine like terms: -4x + -6x = -10x 3 + -10x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -10x = -7 + 0 3 + -10x = -7 Add '-3' to each side of the equation. 3 + -3 + -10x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = -7 + -3 -10x = -7 + -3 Combine like terms: -7 + -3 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 | | 1.25m*7=43.25 | | 2x^2dy=(3xy-y^2)dx | | X+1.5x+0.5x=75 | | sqrt(3x^2+4)-2x=0 | | 4-15=-7 | | -4+3x=20x+9 | | X+1.5x+0.5x= | | l+2l-1+2l+1=30 | | log(x)+log(x-5)=log(5x) | | -4(j+2)=5(j-3) | | c+(3c)+(2.5c)=60 | | (7-x)(x^2+20)= | | (x-3)=50 | | 8+2.50x=30 | | 6x+6=-8+2x+22 | | 0.23(10000)-0.04y=0.06(y+10000) | | 12-4m=36-12m |